Proposed Method for Shoot-Through in Three Phase ZSI and Comparison of Different Control Techniques - Byamakesh Nayak; Saswati Swapna Dash; Subrat Kumar (Institute of Advanced Engineering and Science, 2014)
This paper presented the new methodology for different control techniques applied to three phase Z-source inverter for minimisation of switching losses. The procedure for proposed control techniques and its effects on the performance of operation of three phase Z-source inverter are analyzed. The graphs for voltage gain and voltage stress are drawn for different control methods. The flow-chart for the symmetrical and unsymmetrical control techniques for creating pulse signals for switches of three phase inverter are shown. All the methods are studied and compared with each other. The Total harmonic distortion (THD) of output voltage of both the control methods has been analyzed using FFT analysis. The experiments done and the results shown for capacitor voltage, load current and load line voltage for simple boost and constant boost control techniques are presented using MATLAB/ Simulink.DOI: http://dx.doi.org/10.11591/ijpeds.v5i1.6180